Detection of Shiga toxin-producing Escherichia coli by sandwich enzyme-linked immunosorbent assay using chicken egg yolk IgY antibodies - Parma, Yanil R.; Chacana, Pablo A.; Lucchesi, Paula M.; Roge, Ariel; Granobles Velandia, Claudia V.; Krüger, Alejandra; Parma, Alberto E.; Fernandez Miyakawa, Mariano E. (Frontiers in Cellular and Infection Microbiology, 2012)
Enterohemorrhagic Escherichia coli (EHEC), a subset of Shiga toxin producing E. coli (STEC) is associated with a spectrum of diseases that includes diarrhea, hemorrhagic colitis and a life-threatening hemolytic-uremic syndrome (HUS). Regardless of serotype, Shiga toxins (Stx1 and/or Stx2) are uniformly expressed by all EHEC, and so exploitable targets for laboratory diagnosis of these pathogens. In this study, a sandwich ELISA for determination of Shiga toxin (Stx) was developed using anti-Stx2B subunit antibodies and its performance was compared with that of the Vero cell assay and a commercial immunoassay kit. Chicken IgY was used as capture antibody and a HRP-conjugated rabbit IgG as the detection antibody. The anti-Stx2B IgY was harvested from eggs laid by hens immunized with a recombinant protein fragment. Several parameters were tested in order to optimize the sandwich ELISA assay, including concentration of antibodies, type and concentration of blocking agent, and incubation temperatures. Supernatants from 42 STEC strains of different serotypes and stx variants, including stx2EDL933, stx2vha, stx2vhb, stx2g, stx1EDL933, and stx1d were tested. All Stx variants were detected by the sandwich ELISA, with a detection limit of 115 ng/ml Stx2. Twenty three strains negative for stx genes, including different bacteria species, showed no activity in Vero cell assay and produced negative results in ELISA, except for two strains. Our results show that anti-Stx2B IgY sandwich ELISA could be used in routine diagnosis as a rapid, specific and economic method for detection of Shiga toxin-producing E. coli.